2019
DOI: 10.3390/met9121325
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Corrosion Resistance to H2S in the Welded Joints of X80 Pipeline Steel

Abstract: The microstructure and corrosion resistance in H2S environments for various zones of X80 pipeline steel submerged arc welded joints were studied. The main microstructures in the base metal (BM), welded metal (WM), coarse-grained heat-affected zone (CGHAZ), and fine-grained heat-affected zone (FGHAZ) were mainly polygonal ferrite and granular bainite; acicular ferrite with fine grains; granular bainite, ferrite, and martensite/austenite constituents, respectively. The corrosion behavior differences resulted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In steel, an increased level of corrosive-aggressive non-metallic inclusions can intensify local corrosion processes in the base metal and HAZ. Nanoscale corrosive-aggressive non-metallic inclusions and complex precipitates consisting of oxide and carbonitride components can further decrease the corrosion resistance of the metal in the HAZ [28]. The corrosion behavior in the heat-affected zone (HAZ) was quite different from that in the weld metal (WM) and base metal (BM).…”
Section: Discussionmentioning
confidence: 99%
“…In steel, an increased level of corrosive-aggressive non-metallic inclusions can intensify local corrosion processes in the base metal and HAZ. Nanoscale corrosive-aggressive non-metallic inclusions and complex precipitates consisting of oxide and carbonitride components can further decrease the corrosion resistance of the metal in the HAZ [28]. The corrosion behavior in the heat-affected zone (HAZ) was quite different from that in the weld metal (WM) and base metal (BM).…”
Section: Discussionmentioning
confidence: 99%
“…Since the presence of hydrogen is difficult to detect, the enrichment of S in the vicinity of the crack (Figure 12) reflects that hydrogen atoms do play a role in the propagation of the cracks, which was supposed to induce the occurrence of HE and lead to a reduction in the fracture toughness of the welded joint in the H 2 S-containing environment. Wang et al [25] investigated the corrosion resistance of X80 pipeline steel submerged arc-welded joints to H 2 S in terms of electrochemical corrosion tests and the results showed that the FGHAZ dominated by PF had the best H 2 S corrosion resistance, followed by the WM composed of fine AF, while the CGHAZ consisted of GF and some M-A constituents had the worst H 2 S corrosion resistance. Moreover, it was reported that the bainite in the CGHAZ had the lowest open-circuit potential and it was most susceptible to being corroded during the H 2 S electrochemical corrosion process [25].…”
Section: Fracture Toughness Deterioration Of the Joint In H 2 S Conta...mentioning
confidence: 99%
“…Wang et al [25] investigated the corrosion resistance of X80 pipeline steel submerged arc-welded joints to H 2 S in terms of electrochemical corrosion tests and the results showed that the FGHAZ dominated by PF had the best H 2 S corrosion resistance, followed by the WM composed of fine AF, while the CGHAZ consisted of GF and some M-A constituents had the worst H 2 S corrosion resistance. Moreover, it was reported that the bainite in the CGHAZ had the lowest open-circuit potential and it was most susceptible to being corroded during the H 2 S electrochemical corrosion process [25]. The occurrence of GB and LB was thought to cause CGHAZ to exhibit the weakest resistance to H 2 S corrosion.…”
Section: Fracture Toughness Deterioration Of the Joint In H 2 S Conta...mentioning
confidence: 99%
“…The free potential of the HAZ is close to the coupling potential, so there is almost no galvanic interaction. Jian-bao Wang et al (Wang et al, 2019). studied the hydrogen sulfide corrosion resistance of X80 pipeline steel welded joint.…”
Section: Introductionmentioning
confidence: 99%